Harvesting Sustainability: Transforming Rice Straw Wastes into Eco-Friendly Silica Gel - Aprisilia Risky Wijaya; Gazali Majid; Dede Ulfah; Said, Ahmad; Ramadhani; Musawwa, Muhammad Miqdam (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2024)
The vast quantities of rice straw residue generated every year present both a challenge and an opportunity. To address the challenge, this work took the opportunity by transforming rice straw waste into eco-friendly silica gel. Synthesis of rice straw-based silica gel was via sol-gel method with the calcination temperature of 700 oC for 2 h and the addition of sodium hydroxide 2 molar. Characteristics of silica gel and its raw material have been investigated using several techniques such as FTIR, XRD, SEM, and BET surface area. The synthesized silica gel showed obvious peaks of Si-O-Si and O-H, aggregated smaller particles, crystal nature, and high surface area. This innovative work contributes to agricultural waste management and the circular economy for a sustainable future.